Performance and risk in the Chinese regional ranking sector: a meta-frontier approach - Li, Yuzhu (2021)
This thesis examines the performance and risk of Chinese commercial banks, with a focus on the Chinese regional commercial banking sector from 2005 to 2015. To that end, cost efficiency, scale economies and loan loss provisioning practices are investigated. We begin our analysis by classifying Chinese provinces into three regions using a novel hybrid hierarchical and k-means clustering method based on provincial macroeconomic conditions. We then estimate pooled and individual cost frontiers, and we test whether Chinese regional commercial banks operate under different technologies. Our likelihood test results reject the common technology assumption in favour of technology heterogeneity. Building on the latter, we adopt a stochastic meta-frontier method to estimate a country meta-frontier that envelops regional frontiers. We find that cost efficiency for regional banks mainly stems from technological gaps between regional frontiers and the country meta-frontier. These gaps can be narrowed through increased foreign bank presence, increased banking sector competition and acceleration in regional urbanisation. Banks in the North-eastern and Coastal regions of China are found to be the most cost-efficient, while banks in the Inland region are found to be the least cost-efficient. In addition, we expand our analysis, and we obtain economies of scale from both the individual frontiers and the meta-frontier. Our comparison suggests that banks in the Inland area would operate at the optimal size if they adopt the meta-frontier technology, while regional banks in the core financial centres would start to enjoy economies of scale when they adopt the meta-frontier technology. We also find that investment banking activities, higher liquidity ratio, and lower credit risk would contribute to economies of scale, while banks’ profitability from traditional lending activities does not seem to impact scale economies.